Acute coronary syndrome with normal ECG and negative biomarkers: Case reports. - C. K. Das; M. S. Tripathi; R. L. Bhanja (Medico Research Chronicles, 2020)
Acute Coronary Syndrome (ACS) is diagnosed in an Emergency Department (ED) with the help of Ischemic symptoms, an abnormal Electro Cardio Gram (ECG) and a positive biomarker like Troponin or CK MB enzyme. Non-ST Elevation Myocardial Infarction (NSTEMI) presents with acute ischemic symptoms and ST depression or T inversion or even a normal ECG but with positive biomarkers. We present two unique cases here of Acute Coronary Syndrome with normal serial ECGs and negative biomarkers even after 6 hours of the index event.